EXPLORING THE ANTIBACTERIAL POTENTIAL OF HALOPHILIC FUNGI AND THEIR SECONDARY METABOLITES: AN EVIDENCE-BASED PERSPECTIVE ON NOVEL ANTIBIOTIC CANDIDATE DEVELOPMENT - Mahadewi, Ni Kadek Wiwik; Nursid, Muhammad; Dewi, Luh Putu Mirah Kusuma; Samirana, Putu Oka (Jurnal Farmasi Kryonaut, 2026)
Antibiotic resistance has emerged as a major global health threat, creating an urgent need for alternative antibacterial sources. Halophilic fungi, which inhabit hypersaline environments, are known to produce unique secondary metabolites with potential antibacterial activity. This review aimed to evaluate the antibacterial potential of halophilic fungi and their secondary metabolites through a structured literature review approach. Relevant articles published between 2015 and 2025 were collected from the Scopus and Google Scholar databases using the keywords “halophilic fungi” and “antibacterial”. Article selection was conducted based on predefined inclusion and exclusion criteria following the PRISMA guidelines. A total of 10 eligible original research articles were analyzed descriptively. The findings show that halophilic fungi produce diverse antibacterial metabolites, including alkaloids, gramicidin S, bisvertinolone, epicoracine, alterperylenol, and (Z)-18-octadec-9-enolide, which exhibit inhibitory activity against both Gram-positive and Gram-negative bacteria. Several metabolites demonstrate antibacterial activity comparable to or higher than standard antibiotics, while low Minimum Inhibitory Concentration (MIC) values indicate strong therapeutic potential. Overall, halophilic fungi represent an underexplored biological resource with significant potential for the development of novel antibacterial agents against bacterial resistance.